Complement activation and effect of eculizumab in scleroderma renal crisis. Issue 30 (July 2016) - Devresse, Arnaud; Aydin, Selda; Le Quintrec, Moglie; Demoulin, Nathalie; Stordeur, Patrick; Lambert, Catherine; Gastoldi, Sara; Pirson, Yves; Jadoul, Michel; Morelle, Johann
Abstract: Background: Scleroderma renal crisis (SRC) is a life-threatening complication of systemic sclerosis characterized by abrupt onset of hypertension, thrombotic microangiopathy, and kidney injury. The mechanisms of the disease remain ill-defined, but a growing body of evidence suggests that activation of the complement system may be involved. Methods: Here, we report the case of a patient presenting with severe SRC and strong evidence of complement activation, both in serum and in the kidney, in the absence of genetic defect of the complement system. Results: Immunofluorescence studies on kidney biopsy showed significant deposits of C1q and C4d in the endothelium of renal arterioles, pointing toward activation of the classical pathway. Because of the dramatic clinical and histological severity, and the lack of response to early treatment with angiotensin-converting enzyme inhibitors, calcium channel blockers and plasma exchange, the patient was treated with the specific C5 blocker eculizumab. Contrarily to conventional treatment, eculizumab efficiently blocked C5b-9 deposition ex vivo and maintained hematological remission. Unfortunately, the patient died from heart failure a few weeks later. Postmortem examination of the heart showed diffuse patchy interstitial fibrosis, the typical lesion of systemic sclerosis-related cardiomyopathy, but normal coronary arteries and myocardial microvasculature. Conclusion: SRC may lead to complement system activation through the classical pathway. Early administration of C5 inhibitor eculizumab may have therapeutic potential in patients with life-threatening SRC refractory to conventional treatment using angiotensin-converting enzyme inhibitors. Abstract : Supplemental Digital Content is available in the text